A novel test case generation method based on program structure diagram. (25th June 2019) - Wu, Xianghu; Qu, Mingcheng; Tao, Yongchao; Wang, Guannan; Dong, Ziyu
At present, embedded software has the problems of test lag, non-visual and low efficiency, depending on the test design of testers. It cannot guarantee the quality of the test cases and cannot guarantee the quality of the test. In this paper, a software program structure diagram model is established to verify the model, and the test points are planned manually. Finally, fill in the contents of the test items, and generate the corresponding set of test cases according to the algorithm, and save them into the database for management. This method can improve the reliability and efficiency of test, ensure the visual tracking and management of the use case, and have a strong auxiliary function to the planning and generation of the test case.